Seismic performance of elevated water tank under earthquake loading - Nurul Atikha, Khariul Abidin (2017)
The elevated water tank is very important structure and it consist various type. Water tank is designed to store quantity of liquid such as liquid petroleum and water to supply to the public or residential area. The design also must resist earthquake loading since Malaysia have been experienced a few earthquake event due to the earthquake loading that occurred in the neighboring countries. Back in 2015, the earthquake has occurred in Ranau, Sabah which affected the building structure and geological changes. However, most of the structure designed in Malaysia did not consider the earthquake loading. So, this study will focused on the seismic performance on reinforced concrete of elevated water tank under earthquake loading. The main objective of this research is to study the seismic behavior of elevated water tank structure in Malaysia region under far field earthquake loading. The structure will be design and simulate by using computer software, SAP2000.